Parents’ Roles and Sex Education Rights for Early Childhood - Adiayati Yumna; Lara Fridani; Yuliani Nurani (International Conferences on Early Childhood Education Proceedings, 2023)
There are various educational rights that must be obtained by children including the right to intellectual education, the right to faith education, the right to moral education, the right to physical education, the right to psychological education, the right to social education and the right to sex education (Ulwan, 2012). Sex education in early childhood is more emphasized on how to provide children with an understanding of the condition of their bodies, gender differences and protecting themselves to avoid all forms of sexual violence. In general, some people in Indonesia, including educators (parents and teachers) still do not understand the importance of sex education for early childhood. This can be seen from the increasing number of cases of sexual violence in Indonesia from the Ministry of Women's Empowerment and Child Protection data for 797 children being a victim throughout January 2022 of the many cases of sexual violence in early childhood the role of parents is very important. This study aims to analyze the role of parents, reveal the fulfillment of the right to sex education for early childhood in society. To analyze this issue, the research method used was a literature study conducted through the role of parents and sex education in early childhood. This study found that parents play an important role in providing sex education to children and just like other rights, the right to sex education is also very important to be given to early childhood.